St. Claire Presbyterian Church, Documents, 1980 - Grady County Historical Society (Valdosta State University Archives and Special Collection, 1980)
This collection of materials relates to St. Claire Presbyterian Church in Grady County, Georgia, and is part of the Churches series within the Grady County Historical Society Collection. It includes handwritten letters, a photograph of the church, the deed to the church’s land, minutes from a meeting held in 1980, newspaper clippings, and a typed letter dated 1985. The original documents are held by the Grady County Historical Society and were provided to Valdosta State University Archives and Special Collections for digitization and online access.
1 PDF, 9 scanned images
Keywords: Church History; Grady County (GA.); History- Societies, etc.; Church records and registers